Evaluating the effect of hydrocephalus cause on the manner of changes in the effective parameters and clinical symptoms of the disease - Gholampour, Seifollah; Fatouraee, Nasser; Seddighi, Amir Saeed; Seddighi, Afsoun (Journal of clinical neuroscience, 2017)
•CSF pressure in various type of hydrocephalus is 5–5.3 times greater than the normal.•Difference between CV and peak of pressure in various types of hydrocephalus is small.•Intensity of clinical symptoms is similar in patients with similar CSF pressure.•Hydrocephalus cause didn’t have notable effect on the intensity of clinical symptoms.•Relation of CSF pressure and volume is 16.7% greater in NCH than CH. In the present study, the heads of 11 normal subjects and 21 patients affected by hydrocephalus due to three different causes were simulated using fluid–structure interaction (FSI). To validate the results, the calculated diagram of CSF velocity in aqueduct of Sylvius (AS) was compared with the similar velocity diagram measured using Cine PC-MRI for the same subject. After ensuring the agreement of results, other outputs such as CSF pressure were calculated non-invasively using FSI. The intracranial pressure and CSF pressure in AS and behind the optic nerve sheath were in patients 5–5.3 times the value in normal subjects and the ventricular system volume in patients was 10.2–11.1 times the value in normal subjects. However, the difference between the coefficient of variation and the maximum value of pressure and volume in different types of hydrocephalus was small. Furthermore, the difference between CSF stroke volumes in various types of hydrocephalus patients was less than 4.4%. Results showed that the intensity of clinical symptoms was similar in patients with similar CSF pressure and the cause of the hydrocephalus disease didn’t have any significant effect on the intensity of patients’ clinical symptoms and the manner of changes in effective parameters on disease. It was also found that the relation of CSF pressure and volume was 16.7% greater in patients with non-communicating hydrocephalus than in patients with communicating hydrocephalus. These results enhance the insight into hydrocephalus bio-mechanism and can help to choose the proper treatment method for hydrocephalus patients.